The use of event logs for collaborative practices reflection. (1st January 2012) - Babič, František; Wagner, Jozef; Paralič, Ján
The aim of this paper is to present an original solution for reflection on collaborative practices within learning or working processes mediated by a virtual environment, from which the events are logged and used for analysis. The stored event logs cover performed user activities or single actions in investigated collaborative environment. On the middleware level several services are implemented to manage effective logging mechanism and to execute straight analytical methods that work with available dataset and provide results in specified format. In described case, timeline-based visualisation has been designed, implemented and evaluated as an attractive and effective solution for students, teachers, researchers and professionals. The explanation of historical data is a core element of the complex evaluation in order to identify positive or negative aspects of used practices.